2015
DOI: 10.1044/2015_ajslp-14-0164
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Processes, and Retrospective Outcomes From an Intensive Comprehensive Aphasia Program

Abstract: ICAPs can have a significant effect on the language impairment and participation of people with aphasia, but further research is required to determine if the effect is comparable to other types of service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 40 publications
0
34
0
1
Order By: Relevance
“…Similarly, several other studies from established clinical and research ICAPs have found that most participants make progress in at least one area when assessed with both impairment and patient-reported outcome measures. 43,57,73,74,112,150 While we know that there are significant quantitative gains following participation in an ICAP occur, we do not know what the stakeholders think about these types of treatment programs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, several other studies from established clinical and research ICAPs have found that most participants make progress in at least one area when assessed with both impairment and patient-reported outcome measures. 43,57,73,74,112,150 While we know that there are significant quantitative gains following participation in an ICAP occur, we do not know what the stakeholders think about these types of treatment programs.…”
Section: Introductionmentioning
confidence: 99%
“…112 Effect sizes were large for the WAB Aphasia Quotient (AQ), Language Quotient (LQ), and Cognitive Quotient (CQ) and moderate for the BNT. Family-reported effect size was large on the CETI and moderate for participantreported CETI, ASHA QCL, and CCRSA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations